Experiência de cárie dentária e presença de estreptococos do grupo mutans em indivíduos com fissuras lábio-palatinas: estudo transversal controlado. - Amanda Beatriz Dahdah Aniceto De Freitas (2011)
This controlled cross-sectional study aimed to compare the caries experience and presence of mutans streptococci in adolescents and young adults with cleft lip and / or palate (CL/P) with a control group without clefts. The association between dental caries experience and biological and environmental factors was also assessed. The study included 30 patients with CL/P (case group) and 30 without CL/P (control group), aged between 12 and 21 years, matched by gender, age, living conditions and use of orthodontic device. Data of family income, contact with fluorides, hygiene, access to dental care, maternal education and contact with sucrose were collected. Visible plaque index, gingival bleeding, DMFT and DMFS, and surfaces with active caries lesions were recorded. Microorganisms were isolated from the biofilm collected to identification of S. mutans and S. Sobrinus by PCR. The data were analyzed using the statistical program SPSS 17.0 Data Editor, with a significance level of 5%. The clinical data were analyzed by the McNemar test to compare dichotomous qualitative variables or by the paired t test for quantitative variables with normal distribution or the Wilcoxon test for quantitative variables with non-normal distribution. The groups were compared for the prevalence of mutans streptococci. Backward stepwise conditional logistic regression test the association between caries experience and independent variables. There was no significant difference between case and control groups for oral hygiene and contact with fluoride. The groups differed significantly with respect to variables: per capita income (p = 0.007), surfaces with active caries (p = 0.024), the decay component of the DMFS index (p = 0.040), visible plaque index (p = 0.000) and gingival bleeding (p = 0.002). S. mutans was observed in 83.34% of the biofilm samples in the case group and 86.67% of the control group; S. sobrinus was present in 6.66% of the biofilm samples in the case group and 10% in the control group. There was no association between the presence of S. mutans or S. sobrinus and caries. The presence of CL/P was associated with caries only when it was measured by DMFS. The use of orthodontic apparatus was positively associated with the DMFT, DMFS, the filled components of DMFT and DMFS. Subjects with CL/P showed a higher caries experience than those without CL/P. Among the studied factors that may influence the caries process, environmental factors were more important than biological factors in determining disease.